2010
DOI: 10.1080/17457300.2010.487154
|View full text |Cite
|
Sign up to set email alerts
|

Machine-related injuries in the US mining industry and priorities for safety research

Abstract: Researchers at the National Institute for Occupational Safety and Health studied mining accidents that involved a worker entangled in, struck by, or in contact with machinery or equipment in motion. The motivation for this study came from the large number of severe accidents, i.e. accidents resulting in a fatality or permanent disability, that are occurring despite available interventions. Accident descriptions were taken from an accident database maintained by the United States Department of Labor, Mine Safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 10 publications
2
63
0
2
Order By: Relevance
“…Previous case-control and cohort studies have examined the effect of some of these transient exposures on occupational injuries, especially concerning machinery and surroundings. However, these studies have not looked at potentially important person-oriented transient risk factors such as perceived time pressure, feeling sick, and having a disagreement with or being distracted by someone, and few studies have studied aspects of work practice eg, non-routine task or altered surroundings (7)(8)(9)(10)(11)(12)(13).…”
Section: Transient Risk Factors Of Acute Occupational Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous case-control and cohort studies have examined the effect of some of these transient exposures on occupational injuries, especially concerning machinery and surroundings. However, these studies have not looked at potentially important person-oriented transient risk factors such as perceived time pressure, feeling sick, and having a disagreement with or being distracted by someone, and few studies have studied aspects of work practice eg, non-routine task or altered surroundings (7)(8)(9)(10)(11)(12)(13).…”
Section: Transient Risk Factors Of Acute Occupational Injuriesmentioning
confidence: 99%
“…As in several other work injury case-cross-over studies, the same hazard period for all transient risk factors was chosen for our study (18,(2)(3)(4)(5)(6)(7)(8)39). However, the hazard period is likely to vary between different transient risk factors, eg, a Informative pairs include injured persons who were exposed previous workday, but not before the injury and vice versa.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Despite the significant reductions in accidents over the last two decades, the number of fatalities and injuries related to moving parts (Chinniah, 2015) and to the conveyor belt remains remarkably high (Groves et al, 2007). According to the data provided by Ruff et al (2011) related to the U.S. mining industry the haul trucks, conveyors and front-end-loaders subcategories account for more than 40% of the fatalities and the accidents attributable to the conveyor represent 10% of all fatalities occurred in the last decade in the mining industry. In addition, even when the injuries are not serious, they result in lost work time; over a fiveyear period (2006)(2007)(2008)(2009)(2010), the average number of lostwork days per injury was 35.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of control of these energies is a common cause of injury on mine sites. For example, Ruff et al reported that 41% of severe injuries across all US mines from 2000 to 2007 were associated with machinery [1]. This proportion may be even higher in some sectors: While Burgess-Limerick and Steiner reported that 46% of injuries in New South Wales underground coal mines from 2006 to 2008 were associated with equipment [2]; Cooke et al [3] reported that 68% of injuries at surface coal mines in NSW from 2005 to 2009 were associated with the operation or maintenance of mobile mining equipment.…”
Section: Introductionmentioning
confidence: 99%